The Structure and Evolution of a Sigmoidal Active Region - Gibson, S. E. (2002)
Solar coronal sigmoidal active regions have been shown to be precursors to some coronal mass ejections. Sigmoids, or S-shaped structures, may be indicators of twisted or helical magnetic structures, having an increased likelihood of eruption. We present here an analysis of a sigmoidal region´s three-dimensional structure and how it evolves in relation to its eruptive dynamics. We use data taken during a recent study of a sigmoidal active region passing across the solar disk (an element of the third Whole Sun Month campaign). While S-shaped structures are generally observed in soft X-ray (SXR) emission, the observations that we present demonstrate their visibility at a range of wavelengths including those showing an associated sigmoidal filament. We examine the relationship between the S-shaped structures seen in SXR and those seen in cooler lines in order to probe the sigmoidal region´s three-dimensional density and temperature structure. We also consider magnetic field observations and extrapolations in relation to these coronal structures. We present an interpretation of the disk passage of the sigmoidal region, in terms of a twisted magnetic flux rope that emerges into and equilibrates with overlying coronal magnetic field structures, which explains many of the key observed aspects of the region´s structure and evolution. In particular, the evolving flux rope interpretation provides insight into why and how the region moves between active and quiescent phases, how the region´s sigmoidicity is maintained during its evolution, and under what circumstances sigmoidal structures are apparent at a range of wavelengths.